2022
DOI: 10.3389/fimag.2022.1039721
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of commonly used methods to determine the concordance between sonography and magnetic resonance imaging: A comparative study

Abstract: IntroductionAn increasing number of studies investigate the influence of training interventions on muscle thickness (MT) by using ultrasonography. Ultrasonography is stated as a reliable and valid tool to examine muscle morphology. Researches investigating the effects of a training intervention lasting a few weeks need a very precise measurement since increases in MT can be assumed as small. Therefore, the aim of the present work was to investigate the concordance between MT via sonography and muscle cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…Sonography is the most used assessment to investigate hypertrophy effects because of its relatively low cost and time-efficiency, and is a valid and reliable procedure to investigate MTh and MCSA ( Mendis et al, 2010 ; Betz et al, 2021 ). Nevertheless, there are studies showing limitations of sonography especially because of subjective influence of pressure of the transducer and no real standardization ( Hebert et al, 2009 ; English et al, 2012 ; Warneke et al, 2022e ), which were confirmed in present study showing high %-SDs for changes in MTh of the control group. However, the ICC in the present study is very high for the obtained measures, providing confidence in the results.…”
Section: Discussionsupporting
confidence: 83%
“…Sonography is the most used assessment to investigate hypertrophy effects because of its relatively low cost and time-efficiency, and is a valid and reliable procedure to investigate MTh and MCSA ( Mendis et al, 2010 ; Betz et al, 2021 ). Nevertheless, there are studies showing limitations of sonography especially because of subjective influence of pressure of the transducer and no real standardization ( Hebert et al, 2009 ; English et al, 2012 ; Warneke et al, 2022e ), which were confirmed in present study showing high %-SDs for changes in MTh of the control group. However, the ICC in the present study is very high for the obtained measures, providing confidence in the results.…”
Section: Discussionsupporting
confidence: 83%
“…However, efforts were made to ensure an equal sex distribution, as well as training status. Furthermore, sonography for measuring hypertrophy should be interpreted critically (Warneke et al 2022d ), especially if using just one measurement point. It is recommended to apply more than one spot for measuring muscle thickness via sonography to increase validity (Nunes et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of Morphological Parameters. Since Warneke et al (43) pointed out limited objectivity and accuracy of sonography measurements to determine MTh, measuring of MCSA using the gold standard method of magnetic resonance imaging (MRI) was included to the measurement procedure to confirm results from sonography. To maximize standardization, the posttest was performed at the same time of the day as the pretest.…”
Section: Methodsmentioning
confidence: 99%